2023
DOI: 10.3390/cells12040519
|View full text |Cite
|
Sign up to set email alerts
|

Interplays of AMPK and TOR in Autophagy Regulation in Yeast

Abstract: Cells survey their environment and need to balance growth and anabolism with stress programmes and catabolism towards maximum cellular bioenergetics economy and survival. Nutrient-responsive pathways, such as the mechanistic target of rapamycin (mTOR) interact and cross-talk, continuously, with stress-responsive hubs such as the AMP-activated protein kinase (AMPK) to regulate fundamental cellular processes such as transcription, protein translation, lipid and carbohydrate homeostasis. Especially in nutrient st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…Some reports suggested that the AMPK/mTOR signaling pathway was implicated in the regulation of autophagy 33 , 34 . Under stress conditions such as energy starvation, AMPK is activated as a sensor of energy molecules to regulate autophagy 35 and is a positive regulator of autophagy that actively regulates autophagy by inhibiting mTOR activity 36 . The mTOR is a negative regulator of autophagy that inhibits autophagy by phosphorylating ULK1 to maintain it in an inactive state 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggested that the AMPK/mTOR signaling pathway was implicated in the regulation of autophagy 33 , 34 . Under stress conditions such as energy starvation, AMPK is activated as a sensor of energy molecules to regulate autophagy 35 and is a positive regulator of autophagy that actively regulates autophagy by inhibiting mTOR activity 36 . The mTOR is a negative regulator of autophagy that inhibits autophagy by phosphorylating ULK1 to maintain it in an inactive state 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cellular autophagy can be divided into four distinct stages: autophagic vesicle precursor formation, auto phagosome membrane formation and extension, lysosome closure and fusion, and intracapsular degradation [ 14 ]. While the majority of our understanding of autophagy has been gleaned from studies in yeast, where approximately 30 autophagy-related genes have been identified, it is important to note that the autophagic process involves a complex interplay of signaling molecules and pathways [ 15 ].…”
Section: Autophagy Overviewmentioning
confidence: 99%
“…The regulation of TORC1 signaling pathway is involved in lifespan extension in various species, such as yeast, nematode, fly, and mammals (Bjedov & Rallis, 2020; Fontana et al, 2010; Santos et al, 2016). Similar to other organisms, in fission yeast, the inhibition of TORC1 results in lifespan extension, and it is thought that decreased translation level, increased translational fidelity, and induction of autophagy are involved in the longevity mechanism (Alao et al, 2023; Martinez‐Miguel et al, 2021; Rodríguez‐López et al, 2020). Additionally, some phenotypes of the TORC1 inhibition, including CLS extension and sexual differentiation, are observed during the overexpression of Ecl family genes (Ohtsuka, Imada, et al, 2022; Ohtsuka et al, 2021a; Otsubo et al, 2017).…”
Section: Signal Network Involved In Ecl Family Protein Inductionmentioning
confidence: 99%